TOWARD LOW-CARBON TROPICAL BUILDINGS: A SYSTEMATIC REVIEW OF BIO-BASED WASTE MATERIALS FOR THERMAL INSULATION - Noveryna Dwika Reztrie; Larasati, Dewi; Tambunan, Lily (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
Aims: This study aims to analyze experimental approaches used to evaluate the thermal insulation performance of bio-based wall materials derived from agro-industrial waste, with a specific focus on Palm Oil Fuel Ash (POFA) and eggshell powder, in the context of sustainable tropical building applications. Methodology and results: This study employed a Systematic Literature Review (SLR) consisting of three primary stages: a comprehensive search across reputable databases (Scopus, ScienceDirect, and Google Scholar), article selection based on predefined inclusion criteria, and thematic analysis of 78 eligible studies. The review focused on experimental methods for evaluating thermal performance, including thermal conductivity (Hot Disk, Guarded Hot Plate), specific heat capacity (DSC), surface reflectance (UV-VIS), and chemical-microstructural analyses (TGA, SEM-EDS, XRD). Findings indicate that POFA and eggshell powder exhibit thermal conductivity values between 0.12–0.25 W/m·K, attributed to microporous structures and high SiO₂ or CaCO₃ content. Nonetheless, the integration of these laboratory findings with building energy simulations and the consideration of tropical, specific variables, such as humidity and solar radiation, remains notably limited in existing literature. Conclusion, significance and impact study: This study identifies critical methodological gaps in current research on bio-based thermal insulation materials and underscores the need for a more integrated evaluation framework. Specifically, it recommends combining laboratory testing with building energy simulation to enhance the validity and applicability of findings. Such an approach is essential for advancing the reliable implementation of agro-industrial bio-waste materials, such as POFA and eggshell powder, in sustainable tropical architecture. The proposed integration not only strengthens the scientific foundation of material performance assessment but also contributes to more climate-responsive and low-carbon building design strategies in the Global South.